Correction: Corrigendum: Regulation of PERK–eIF2α signalling by tuberous sclerosis complex-1 controls homoeostasis and survival of myelinating oligodendrocytes - Minqing Jiang (Nature Portfolio, 2016)
Nature Communications 7: Article number: 12185 (2016); Published: 15 July 2016; Updated: 22 November 2016 The GEO accession number provided in this article is incorrect; the correct number is GSE74893.